UJI LABORATORIUM PENULARAN TRANSOVARIAL PADA NYAMUK Aedes aegypti - , GUNTUR BENEDICT HUTADJULU ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background : Aedes aegypti is one of the vectors causing Dengue Hemorrhagic Fever (DHF) that feeds on human blood suffering from DHF and transmit it to another healthy human. The ability of Dengue (DEN) virus to survive in nature is due to 2 mechanisms: horizontal transmission among viremic vertebratae infected by Aedes mosquitos and vertical (transovarial) transmission from infected female mosquito to another generation. Objectives : To know the differences in next generationâs viral carriage, percentage of mosquito descendants carrying DEN virus, and the distribution of DEN virus in mosquito body among DEN virus-infected mosquitos and uninfected mosquitos. Methods : The research was a quasi-experimental study with posttest-only design with control group. The research was done on 53 second-generation female Aedes aegypti mosquitos which are divided into two groups. Between the 2 groups we observed the transovarial transmission distribution with immunocytochemistry method, Streptavidin Biotin Peroxidase Complex (SBPC), in mosquitos aged 1-7 days. The results were then analyzed with Fisher formula. Results : The results obtained was 100% of the DEN virusinfected mosquitos and 85.7% of uninfected mosquitos carrying DEN virus transovarially into next generation. The virus was evenly distributed from day 1 to 7 in brains, thorax, salivary gland, gastric epithelial cells, and ovarium of the infected mosquitos, while in uninfected mosquitos the distribution was uneven. Conclusion : There was no difference in next mosquito generationâs transovarial infection among DEN virus-infected and uninfected Aedes aegypti mosquitos.